Entropy Prussian blue-based positive electrode material in sodium ion battery and preparation method of entropy Prussian blue-based positive electrode material
By introducing complexing agent and medium-entropy component design into the entropy Prussian blue-based cathode material in sodium ion batteries, the problem of insufficient energy density and structural stability of the cathode material in the prior art is solved, and a sodium ion battery with high energy density, excellent cycle stability and long life is achieved.
Patent Information
- Application Number
- CN202411717469.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-28
AI Technical Summary
The energy density and structural stability of existing sodium ion battery cathode materials still need to be improved, especially due to the reduction of sodium storage sites and the slowdown of sodium ion diffusion rate due to high content of anion vacancies and coordination water molecules.
By introducing complexing agents into the entropy Prussian blue-based cathode material in sodium ion batteries, the nucleation and growth rate are slowed down, the formation of anion vacancy and coordination water molecules is inhibited, and through the design of the medium-entropy component, the Jahn-Teller lattice distortion effect and sodium storage phase transition behavior are suppressed by the design of the medium-entropy component.
It achieves high energy density, high power density and excellent cycling stability, significantly enhances the crystal structure stability of the positive electrode material, and extends the cycle life of the sodium ion battery.
Smart Images

Figure CN119706873A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to an entropic Prussian blue-based positive electrode material for a sodium ion battery and a preparation method thereof. Background Art
[0002] In recent years, due to the overexploitation of fossil energy and energy shortages, green and clean energy such as solar energy, wind energy and tidal energy have received widespread attention. However, these energy sources are easily restricted by the influence of time and space such as climate environment and geographical location, and thus have shortcomings such as intermittency and volatility. Therefore, there is an urgent need to develop an efficient large-scale energy storage technology.
[0003] Currently, lithium-ion batteries, as an electrochemical energy storage device, have been widely used in portable electronic devices and electric vehicles due to their high energy density and long service life. However, due to the shortage of lithium resources and high prices, lithium-ion batteries are difficult to meet the growing market demand and cannot be used in large-scale energy storage devices. Therefore, it is imperative to develop alternatives to lithium-ion batteries.
[0004] Sodium-ion batteries have attracted widespread attention in the field of energy storage due to their abundant resources, low cost, high safety and low-temperature performance. However, the large ionic radius of sodium ions has become a key technical bottleneck restricting the development of high-performance cathode materials. The cathode materials of sodium-ion batteries mainly include four categories: layered transition metal oxides, Prussian blue analogs, polyanion compounds and organic materials. Among them, Prussian blue analogs have a three-dimensional network framework structure, which is conducive to the storage and reversible deintercalation of large-sized sodium ions, thereby obtaining excellent cycle stability; in addition, its composition and structure are easy to control, so it can also achieve high operating voltage and energy density.
[0005] However, there are high levels of anion vacancies and coordinated water molecules in the crystal structure of Prussian blue-based materials, which will cause a reduction in sodium storage sites, a slowdown in the diffusion rate of sodium ions, and a collapse of the crystal structure. Chinese patent application CN116354364A discloses a medium-entropy sodium-ion battery cathode material and a preparation method thereof. The chemical formula of the medium-entropy sodium-ion battery cathode material is A x M y [Fe(CN)6] 1-z nH2O, where 1≤x≤2, 0<y<1, 0≤z<1, 0<n≤3.5, A includes Na and / or K; M includes Mn, Fe and other metal elements. By introducing two or more non-Mn-based metal ions, the lattice stress and structural damage caused by the Jahn-Teller effect of Mn-based materials can be alleviated, and the cycle performance of electrode materials can be improved. However, in the chemical formula of the positive electrode material of the sodium ion battery, 0≤z<1, indicating that the system material has a high content of [Fe(CN)6] 4-Anion vacancies, and only other inert metal ions are used to enhance the structural stability of Mn / Fe-based Prussian blue, and its energy density and structural stability still need to be improved. Another Chinese patent application CN116768236A of the inventor discloses a high-entropy Prussian blue-based positive electrode material for sodium ion batteries and a preparation method thereof. The chemical formula of the positive electrode material is Na x M[Fe(CN)6], wherein 0≤x≤2; the M comprises five or more transition metal elements. The high entropy material is designed to suppress the sodium storage phase transition behavior, but the introduction of multiple inert metal ions leads to a low specific capacity.
[0006] In view of this, the development of a Prussian blue-based positive electrode material with high specific energy and long cycle life has important scientific significance and commercial value for the development of sodium-ion batteries. Summary of the invention
[0007] The purpose of the present invention is to provide a sodium ion battery medium entropy Prussian blue-based cathode material and a preparation method thereof, using a complexing agent to slow down the nucleation and growth rate of the Prussian blue-based cathode material, thereby effectively inhibiting the generation of [Fe(CN)6] anion vacancies and coordinated water molecules in the crystal structure; based on the design of medium entropy components, the entropy stabilization and multi-element synergistic effects are used to inhibit the severe Jahn-Teller lattice distortion effect and complex sodium storage phase transition behavior during the sodium storage process. The synthesized medium entropy low-defect Prussian blue-based cathode material has the advantages of high energy density, high power density and excellent cycle stability.
[0008] To achieve the above object, the present invention adopts the following technical solution.
[0009] On the one hand, the present invention provides a sodium ion battery entropy Prussian blue-based cathode material, the molecular formula of which is Na x M[Fe(CN)6] y , wherein 0≤x≤2, 0.9≤y≤1, M is three or four transition metal ions, and Fe is a divalent iron ion or a trivalent iron ion.
[0010] Furthermore, the M is three or four transition metal ions selected from the group consisting of cobalt, iron, nickel, manganese, zinc, copper, vanadium, titanium and chromium ions.
[0011] On the other hand, the present invention also provides a method for preparing the entropic Prussian blue-based cathode material in the sodium ion battery, which comprises the following steps:
[0012] 1) dissolving a transition metal salt, an inorganic sodium salt and a complexing agent in deionized water to form a solution A; and dissolving sodium ferrocyanide or sodium ferrocyanide in deionized water to form a solution B;
[0013] 2) adding solution A dropwise into solution B to form a mixed solution; stirring the mixed solution at a certain temperature and standing for aging, obtaining a precipitate by solid-liquid separation, washing the precipitate, and vacuum drying to obtain an entropic Prussian blue-based positive electrode material for a sodium ion battery.
[0014] Furthermore, the transition metal salt described in step 1) is three or four of cobalt salts, iron salts, nickel salts, manganese salts, zinc salts, copper salts, vanadium salts, titanium salts, and chromium salts, wherein the salt is one or more of sulfates, chlorides, nitrates, and acetates.
[0015] Furthermore, the complexing agent in step 1) is one or more of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, sodium citrate, disodium ethylenediaminetetraacetate, and sodium pyrophosphate.
[0016] Furthermore, the inorganic sodium salt in step 1) is one or more of sodium chloride, sodium sulfate, sodium carbonate and sodium acetate.
[0017] Furthermore, in step 1), the molar ratio of the complexing agent to the sodium ferrocyanide or sodium ferrocyanide is 0.5-10, and the molar ratio of the inorganic sodium salt to the sodium ferrocyanide or sodium ferrocyanide is 0-100.
[0018] Further, in step 2), solution A is dripped dropwise into solution B at a flow rate of 0.05 to 2 ml / min at a temperature of 20 to 80°C.
[0019] Furthermore, in step 2), the temperature for stirring and standing for aging is 20 to 80° C., and the reaction time is 2 to 36 hours.
[0020] Furthermore, in step 2), vacuum drying is performed at a temperature of 40 to 150° C. for a drying time of 6 to 36 hours.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The fast reaction rate of the coprecipitation method is greatly slowed down by utilizing the complexing effect of the complexing agent and the transition metal ions. The crystal nucleation and growth rates are slowed down by the orderly coordination of the transition metal ions and the cyanide ions, and the coordination tendency of the hydrated ions and N is controlled, so that the vacancy defects and the content of coordinated water molecules in the crystal structure are effectively controlled. The synthesized Prussian blue-based material has a high reversible specific capacity, good rate performance and cycle stability when used as the positive electrode material of sodium ion batteries.
[0023] (2) The crystal structure stability of Prussian blue-based cathode materials is significantly enhanced by utilizing the intermediate entropy stabilization and multi-element synergistic effects, thereby suppressing the lattice distortion caused by sodium ion insertion and extraction during the electrochemical cycle to a large extent, thereby achieving an excellent cycle life for sodium ion batteries.
[0024] (3) The synthesis process of the present invention is simple and universal, green and environmentally friendly, and the raw material cost is low, so it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The intermediate entropy Prussian blue-based cathode material Na2Mn prepared in Example 1 of the present invention 1 / 6 Fe 1 / 6 Ni 2 / 3 X-ray diffraction (XRD) pattern of [Fe(CN)6];
[0026] Figure 2 The intermediate entropy Prussian blue-based cathode material Na2Mn prepared in Example 1 of the present invention 1 / 6 Fe 1 / 6 Ni 2 / 3 Scanning electron microscopy (SEM) image of [Fe(CN)6];
[0027] Figure 3 The intermediate entropy Prussian blue-based cathode material Na2Mn prepared in Example 1 of the present invention 1 / 6 Fe 1 / 6 Ni 2 / 3 [Fe(CN)6] at 10mAg -1 First charge and discharge curves at current density;
[0028] Figure 4 The intermediate entropy Prussian blue-based cathode material Na2Mn prepared in Example 1 of the present invention 1 / 6 Fe 1 / 6 Ni 2 / 3 [Fe(CN)6] at 100mAg -1 Cycling performance diagram under current density;
[0029] Figure 5 The intermediate entropy Prussian blue-based cathode material Na2Mn prepared in Example 1 of the present invention 1 / 6 Fe 1 / 6 Ni 2 / 3 Rate performance diagram of [Fe(CN)6].
[0030] Figure 6 The medium entropy Prussian blue-based cathode material Na2Fe prepared in Example 2 of the present invention 1 / 3 Co 1 / 3 Ni 1 / 3X-ray diffraction (XRD) pattern of [Fe(CN)6];
[0031] Figure 7 The medium entropy Prussian blue-based cathode material Na2Fe prepared in Example 2 of the present invention 1 / 3 Co 1 / 3 Ni 1 / 3 Scanning electron microscopy (SEM) image of [Fe(CN)6];
[0032] Figure 8 The medium entropy Prussian blue-based cathode material Na2Fe prepared in Example 2 of the present invention 1 / 3 Co 1 / 3 Ni 1 / 3 [Fe(CN)6] at 10mAg -1 First charge and discharge curves at current density;
[0033] Fig. 9 The medium entropy Prussian blue-based cathode material Na2Fe prepared in Example 2 of the present invention 1 / 3 Co 1 / 3 Ni 1 / 3 [Fe(CN)6] at 10mAg -1 Cycling performance diagram under current density; DETAILED DESCRIPTION
[0034] The present invention will be further described in detail and clearly in conjunction with specific embodiments and the accompanying drawings of the specification, but the present invention is not limited thereto. It should be understood that the specific embodiments presented below are only used to explain the present invention and are not used to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined in any suitable manner as long as they do not conflict with each other, for example, different embodiments and technical solutions can be formed by combining different specific technical features. In order to avoid unnecessary repetition, the various possible combinations of the specific technical features in the present invention are no longer described separately, but they all belong to the scope of protection of the present invention.
[0035] Example 1
[0036] (1) 5 / 6 mmol manganese chloride, 5 / 6 mmol ferrous chloride, 10 / 3 mmol nickel chloride, 10 g sodium chloride, 25 mmol disodium ethylenediaminetetraacetate and 1 g polyvinylpyrrolidone were dissolved in 50 ml deionized water to form a uniform solution A; 5 mmol sodium ferrocyanide was dissolved in 50 ml deionized water to form a uniform solution B;
[0037] (2) Solution A was dripped into solution B at a rate of 0.2 ml / min at 40°C in a water bath to form a uniform solution; the mixed solution was stirred at 60°C for 8 h, the precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 80°C for 12 h under vacuum to obtain a medium-entropy Prussian blue-based cathode material (Na2Mn 1 / 6 Fe 1 / 6 Ni 2 / 3 [Fe(CN)6]).
[0038] The Prussian blue-based cathode material, acetylene black, and PVDF (polyvinylidene fluoride) were dissolved in NMP (N-methylpyrrolidone) at a mass ratio of 7:2:1 to form a uniform slurry, which was then coated on aluminum foil and vacuum dried at 80°C before cutting to obtain the cathode electrode sheet. Metallic sodium was used as the anode, glass fiber was selected as the separator, and 1M NaClO4 solution was used as the electrolyte (the solvent was 1:1 EC / DEC containing 5% FEC), and a half-cell was assembled in a glove box, and electrochemical tests were performed at an operating voltage of 2 to 4.3V and current densities of different sizes.
[0039] like Figure 1 The intermediate entropy Na2Mn prepared in this example is shown. 1 / 6 Fe 1 / 6 Ni 2 / 3 The X-ray diffraction (XRD) pattern of the [Fe(CN)6] positive electrode material shows that the material has a typical face-centered cubic structure. Figure 2 Shown is a scanning electron microscope (SEM) image of the material, the morphology is uniform nanocubes; Figure 3 For this material at 10mAg -1 The first charge and discharge curve under the current density, the first discharge capacity is 67.8 mAh g -1 ; Figure 4 Given at 100mAg -1 The cycling performance at the current density is as high as 62.9 mAh g -1 , the capacity retention rate is 81.62% after 2000 cycles. Figure 5 The results show that the material has good thermal conductivity at 10, 20, 50, 100, 200 and 500 mAg. -1 The rate performance under the current density shows a high rate capacity. It can be seen that the medium-entropy Prussian blue-based positive electrode material prepared in this embodiment has a high reversible specific capacity, excellent cycle stability and good rate performance.
[0040] Example 2
[0041] (1) 5 / 3 mmol ferrous sulfate, 5 / 3 mmol cobalt sulfate, 5 / 3 mmol nickel sulfate, 10 g sodium chloride, 10 mmol disodium ethylenediaminetetraacetate and 1 g polyvinylpyrrolidone were dissolved in 50 ml deionized water to form a uniform solution A; 5 mmol sodium ferrocyanide was dissolved in 50 ml deionized water to form a uniform solution B;
[0042] (2) Solution A was dripped into solution B at a rate of 1 ml / min at 80°C in a water bath to form a uniform solution; the mixed solution was stirred at 80°C for 2 h and allowed to stand for 6 h, the precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 100°C for 12 h under vacuum to obtain a low-defect Prussian blue-based cathode material (Na2Fe 1 / 3 Co 1 / 3 Ni 1 / 3 [Fe(CN)6]).
[0043] like Figure 6 The intermediate entropy Na2Fe prepared in this example is shown. 1 / 3 Co 1 / 3 Ni 1 / 3 The X-ray diffraction (XRD) pattern of the [Fe(CN)6] positive electrode material shows that the material has a typical face-centered cubic structure. Figure 7 Shown is a scanning electron microscope (SEM) image of the material, the morphology is uniform nanoparticles; Figure 8 For this material at 10mAg -1 The first charge and discharge curve under the current density, the first discharge capacity is 106.6 mAh g -1 ; Fig. 9 Given at 10mAg -1 Cycling performance under current density, the capacity retention value after 80 cycles is 81.5 mAh g -1 It can be seen that the medium-entropy Prussian blue-based cathode material prepared in this example has a high reversible specific capacity and excellent cycle stability.
[0044] Example 3
[0045] (1) 5 / 3 mmol manganese nitrate, 5 / 3 mmol iron nitrate, 5 / 3 mmol cobalt nitrate, 10 g sodium chloride, 25 mmol sodium carboxymethyl cellulose and 1 g polyvinyl pyrrolidone were dissolved in 50 ml deionized water to form a uniform solution A; 5 mmol sodium ferrocyanide was dissolved in 50 ml deionized water to form a uniform solution B;
[0046] (2) Solution A was dripped into solution B at a rate of 0.5 ml / min at 60°C in a water bath to form a uniform solution; the mixed solution was stirred at 40°C for 5 h and allowed to stand for 24 h, the precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 60°C for 18 h under vacuum to obtain a low-defect Prussian blue-based cathode material (Na2Mn 1 / 3 Fe 1 / 3 Co 1 / 3 [Fe(CN)6]).
[0047] Example 4
[0048] (1) Dissolve 2.5 mmol manganese chloride, 2.5 mmol nickel chloride, 2.5 mmol zinc chloride, 2.5 mmol copper chloride, 20 g sodium chloride, and 20 mmol sodium citrate in 50 ml deionized water to form a uniform solution A; dissolve 10 mmol sodium ferrocyanide in 50 ml deionized water to form a uniform solution B.
[0049] (2) Solution A was dripped into solution B at a rate of 2 ml / min at 40°C in a water bath to form a uniform solution; the mixed solution was stirred at 50°C for 5 h and allowed to stand for 12 h, the precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 100°C for 12 h under vacuum to obtain a low-defect Prussian blue-based cathode material (Na2Mn 1 / 4 Ni 1 / 4 Zn 1 / 4 Cu 1 / 4 [Fe(CN)6]).
[0050] Example 5
[0051] (1) 1.5 mmol of ferric acetate, 1.5 mmol of cobalt acetate, 1.5 mmol of copper acetate, 1.5 mmol of titanium trichloride, 12 g of sodium chloride, and 18 mmol of disodium ethylenediaminetetraacetate were dissolved in 50 ml of deionized water to form a uniform solution A; 10 mmol of sodium ferrocyanide was dissolved in 50 ml of deionized water to form a uniform solution B.
[0052] (2) Solution A was dripped into solution B at a rate of 1.5 ml / min at 70°C in a water bath to form a uniform solution; the mixed solution was stirred at 70°C for 12 h, the precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 120°C for 8 h under vacuum to obtain a low-defect Prussian blue-based cathode material (NaFe 1 / 4 Co 1 / 4 Cu 1 / 4 Ti 1 / 4 [Fe(CN)6]).
[0053] Example 6
[0054] (1) Dissolve 1 mmol of manganese nitrate, 1 mmol of ferrous chloride, 1 mmol of cupric acetate, 1 mmol of cobalt chloride, 10 g of sodium chloride, 25 mmol of sodium citrate and 1 g of polyvinyl pyrrolidone in 50 ml of deionized water to form a uniform solution A; dissolve 5 mmol of sodium ferrocyanide in 50 ml of deionized water to form a uniform solution B.
[0055] (2) Solution A was dripped into solution B at a rate of 0.5 ml / min at 30°C in a water bath to form a uniform solution; the mixed solution was stirred at 60°C for 3 h and allowed to stand for 16 h. The precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 150°C for 6 h under vacuum to obtain a low-defect Prussian blue-based cathode material (Na2Mn 1 / 4 Fe 1 / 4 Co 1 / 4 Cu 1 / 4 [Fe(CN)6]).
[0056] Example 7
[0057] (1) dissolving 2 mmol of manganese nitrate, 2 mmol of ferrous chloride, 0.5 mmol of nickel acetate, and 20 mmol of sodium citrate in 50 ml of deionized water to form a uniform solution A; dissolving 12 mmol of sodium ferrocyanide in 50 ml of deionized water to form a uniform solution B;
[0058] (2) Solution A was dripped into solution B at a rate of 0.8 ml / min at 25°C in a water bath to form a uniform solution; the mixed solution was stirred at 25°C for 6 h and allowed to stand for 24 h, the precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 80°C for 24 h under vacuum to obtain a low-defect Prussian blue-based cathode material (Na2Mn 0.4 Fe 0.4 Ni 0.2 [Fe(CN)6]).
[0059] Example 8
[0060] (1) 2 mmol manganese nitrate, 2 mmol nickel chloride, 0.5 mmol cobalt acetate, and 15 mmol sodium citrate were dissolved in 50 ml deionized water to form a uniform solution A; 14 mmol sodium ferrocyanide was dissolved in 50 ml deionized water to form a uniform solution B;
[0061] (2) Solution A was dripped into solution B at a rate of 1 ml / min in a water bath at 40°C to form a uniform solution; the mixed solution was allowed to stand at 25°C for 24 h, the precipitate was washed three times by alternating centrifugation with deionized water and ethanol, and finally dried at 90°C for 18 h under vacuum to obtain a low-defect Prussian blue-based cathode material (Na2Mn0.4 Ni 0.4 Co 0.2 [Fe(CN)6]).
[0062] It should be noted that the above-described embodiments are only some preferred embodiments of the present invention. A person skilled in the art can make some modifications, improvements, equivalent substitutions based on the principles and embodiments of the present invention to obtain new technical solutions, and these new solutions should obviously also be within the protection scope of the present invention.
Claims
1. A sodium ion battery medium entropy Prussian blue-based cathode material, characterized in that: The molecular formula of the positive electrode material is Na x M[Fe(CN)6] y , wherein 0≤x≤2, 0.9≤y≤1, M is three or four transition metal ions, and Fe is a divalent iron ion or a trivalent iron ion.
2. The sodium ion battery mesotropic Prussian blue-based cathode material according to claim 1, characterized in that: The M is three or four transition metal ions selected from the group consisting of cobalt, iron, nickel, manganese, zinc, copper, vanadium, titanium and chromium ions.
3. The method for preparing the entropic Prussian blue-based positive electrode material for sodium ion batteries according to claim 1 or 2, characterized in that: The following steps are involved: 1) dissolving a transition metal salt, an inorganic sodium salt and a complexing agent in deionized water to form a solution A; and dissolving sodium ferrocyanide or sodium ferrocyanide in deionized water to form solution B; 2) adding solution A dropwise into solution B to form a mixed solution; The mixed solution is stirred at a certain temperature and allowed to stand for aging, and then a precipitate is obtained by solid-liquid separation. The precipitate is washed and vacuum-dried to obtain an entropic Prussian blue-based positive electrode material for a sodium ion battery.
4. The method for preparing the entropic Prussian blue-based cathode material for sodium ion batteries according to claim 3, characterized in that: The transition metal salt described in step 1) is three or four of cobalt salt, iron salt, nickel salt, manganese salt, zinc salt, copper salt, vanadium salt, titanium salt and chromium salt, wherein the salt is one or more of sulfate, chloride, nitrate and acetate.
5. The method for preparing the entropic Prussian blue-based cathode material for sodium ion batteries according to claim 3, characterized in that: The complexing agent described in step 1) is one or more of polyvinyl pyrrolidone, sodium carboxymethyl cellulose, sodium citrate, disodium ethylenediaminetetraacetate, and sodium pyrophosphate.
6. The method for preparing the entropic Prussian blue-based cathode material for sodium ion batteries according to claim 3, characterized in that: The inorganic sodium salt described in step 1) is one or more of sodium chloride, sodium sulfate, sodium carbonate and sodium acetate.
7. The method for preparing the entropic Prussian blue-based cathode material for sodium ion batteries according to claim 3, characterized in that: In step 1), the molar ratio of the complexing agent to the sodium ferrocyanide or sodium ferrocyanide is 0.5-10, and the molar ratio of the inorganic sodium salt to the sodium ferrocyanide or sodium ferrocyanide is 0-100.
8. The method for preparing the entropic Prussian blue-based cathode material for sodium ion batteries according to claim 3, characterized in that: In step 2), solution A is dripped dropwise into solution B at a flow rate of 0.05 to 2 ml / min at a temperature of 20 to 80°C.
9. The method for preparing the entropic Prussian blue-based cathode material for sodium ion batteries according to claim 3, characterized in that: In step 2), the temperature for stirring and standing for aging is 20 to 80° C., and the reaction time is 2 to 36 hours.
10. The method for preparing the entropic Prussian blue-based cathode material for sodium ion batteries according to claim 3, characterized in that: In step 2), vacuum drying is performed at a temperature of 40 to 150° C. for 6 to 36 hours.
Citation Information
Patent Citations
Multi-element Prussian blue sodium ion battery positive electrode material and preparation method thereof
CN112607748A
Ternary cyano framework material as well as preparation method and application thereof
CN113511691A
Prussian blue positive electrode material and preparation method and application thereof
CN116598484A
High-entropy Prussian blue-based positive electrode material of sodium ion battery and preparation method of high-entropy Prussian blue-based positive electrode material
CN116768236A
Positive electrode material, preparation method, application, battery positive electrode and sodium ion battery
CN117038966A